Comparison of CO2 Vertical Profiles in the Lower Troposphere between 1.6 µm Differential Absorption Lidar and Aircraft Measurements Over Tsukuba - Yasukuni Shibata; Chikao Nagasawa; Makoto Abo; Makoto Inoue; Isamu Morino; Osamu Uchino (Sensors, 2018)
A 1.6 μm differential absorption Lidar (DIAL) system for measurement of vertical CO2 mixing ratio profiles has been developed. A comparison of CO2 vertical profiles measured by the DIAL system and an aircraft in situ sensor in January 2014 over the National Institute for Environmental Studies (NIES) in Tsukuba, Japan, is presented. The DIAL measurement was obtained at an altitude range of between 1.56 and 3.60 km with a vertical resolution of 236 m (below 3 km) and 590 m (above 3 km) at an average error of 1.93 ppm. An in situ sensor for cavity ring-down spectroscopy of CO2 was installed in an aircraft. CO2 mixing ratio measured by DIAL and the aircraft sensor ranged from 398.73 to 401.36 ppm and from 399.08 to 401.83 ppm, respectively, with an average difference of −0.94 ± 1.91 ppm below 3 km and −0.70 ± 1.98 ppm above 3 km between the two measurements.